L’espace urbain dans Un Joualonais sa Joualonie de M.‑C. Blais - Éva Pich‑Ponce (Multilinguales)
This study aims to analyse the representation of the city in Un Joualonais sa Joualonie by Marie-Claire Blais. It will highlight the importance that the concepts of alienation and abjection have in the vertical description of the city. This urban setting is characterized by many differences (geographical, social, economic, linguistic, cultural) that condition the relationships among the characters. However, we will see how the borders between social and urban differences hide a wider division, characterized by antagonistic discourses that reflect the actual plurality of Quebec in the 70’s.